Strong seasonal differences of bacterial polysaccharide utilization in the North Sea over an annual cycle. (17th April 2022) - Giljan, Greta; Arnosti, Carol; Kirstein, Inga V.; Amann, Rudolf; Fuchs, Bernhard M.
Summary: Marine heterotrophic bacteria contribute considerably to global carbon cycling, in part by utilizing phytoplankton‐derived polysaccharides. The patterns and rates of two different polysaccharide utilization modes – extracellular hydrolysis and selfish uptake – have previously been found to change during spring phytoplankton bloom events. Here we investigated seasonal changes in bacterial utilization of three polysaccharides, laminarin, xylan and chondroitin sulfate. Strong seasonal differences were apparent in mode and speed of polysaccharide utilization, as well as in bacterial community compositions. Compared to the winter month of February, during the spring bloom in May, polysaccharide utilization was detected earlier in the incubations and a higher portion of all bacteria took up laminarin selfishly. Highest polysaccharide utilization was measured in June and September, mediated by bacterial communities that were significantly different from spring assemblages. Extensive selfish laminarin uptake, for example, was detectible within a few hours in June, while extracellular hydrolysis of chondroitin was dominant in September. In addition to the well‐known Bacteroidota and Gammaproteobacteria clades, the numerically minor verrucomicrobial clade Pedosphaeraceae could be identified as a rapid laminarin utilizer. In summary, polysaccharide utilization proved highly variable over the seasons, both in mode and speed, and also by the bacterial clades involved.